Tingkat Keberhasilan Program Pengembangan Usaha Agribisnis Perdesaan di Kabupaten Ende Provinsi Nusa Tenggara Timur - Philipus N. Supardi; Ketut Budi Susrusa; I Wayan Budiasa (Universitas Udayana, 2015)
Rural Agribusiness Development Program is a breakthrough program of Ministry of Agriculture for poverty reduction and employment, as well as for development gap reduction between central and regional regions and between sub-sectors. Ende Regency is one of beneficiary of Rural Agribusiness Development Program in East Nusa Tenggara province. The objectives of this study are assessing the success rate of the Rural Agribusiness Development Program in Ende Regency and assessing factors affecting the success of Rural Agribusiness Development Program in Ende Regency with survey method. The study population is the Farmers Group Association (GAPOKTAN) as the beneficiary of Rural Agribusiness Development Program in the year of 2010. Sampling is done randomly (random sampling) with a total of 30 GAPOKTAN. Data was analyzed quantitative descriptively and relation analysis with partial least squares (PLS). The success rate of the Rural Agribusiness Development Program in Ende Regency is classified as less successful with the score of 2.1. Simultaneously, all the exogenous factors: Organizational Factor (X1), Rural Agribusiness Development Program Management Factor (X2), Agribusiness Factor (X3), Entrepreneurial Factor (X4), Agribusiness Management Factor (X5), and Leadership Factor (X6) collectively have strong influence towards the success of Rural Agribusiness Development Program. Partially, not all of the six variables affecting the success of the program, in which the Agribusiness variable has no influence towards the success of the Rural Agribusiness Development Program. Suggestions may be submitted to this study are the enhancement of the Farmers Group Association Boards capability as the facilitators by conducting comparative study to regencies or provincies whose Rural Agribusiness Development Programs are successful in conducting trainings, that the business can be developed that absorb labours, intensive supervission of the government and monitoring and evaluation by the regency coordinating team related to financial management.